Annotated catalogue of the click-beetle tribe Senodoniini (Coleoptera: Elateridae: Dendrometrinae) - Kundrata, Robin; Musalkova, Marketa; Prosvirov, Alexander S (Zootaxa, 2018)
An annotated catalogue of the tribe Senodoniini (Coleoptera: Elateridae: Dendrometrinae) is presented. Altogether, 21 extant species are classified in genera Senodonia Laporte, 1838 (20 species) and Sossor Candèze, 1883 (one species). Genus Parallotrius Candèze, 1878 is placed into Dendrometrinae incertae sedis, and Allotriopsis Champion, 1896 is tentatively transferred to Elaterinae: Dicrepidiini. Senodonia bicoloris Vats Chauhan, 1993 is transferred to Arhaphes Candèze, 1860 (Elateridae: Negastriinae) as A. bicoloris (Vats Chauhan, 1993) comb. nov. Senodoniini are distributed in the Himalayas, China and South East Asia. For each taxon we provide synonyms, information on types, type localities, distribution, and bibliography. Additionally, a list of genera earlier classified in Senodoniini but currently placed outside the group is given.
Keywords: Čína; brouci; Coleoptera, Arhaphes, click-beetles, Elateroidea, Dimini, diversity, Negastriinae, Senodonia, Sossor, systematics; rozšíření zvířat; zvířata; China; jihovýchodní Asie; Coleoptera; Asia, Southeastern; Animal Distribution; Animals